PENGARUH KIPAS STIMULASI PERKEMBANGAN ANAK PADA IBU DENGAN POLA ASUH TERHADAP PERKEMBANGAN BALITA DI KOTA BOGOR - Dedes Fitria; Yohana Wulan Rosaria (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Mother's parenting is a factor that is very closely related to the growth and development of children underfive years of age. Health education delivered can use a variety of media including with a child developmentstimulation fan that has a simple shape and attractive color combination, can be attached so that it can beread by many people. Research shows that through aids in the form of a fan stimulation of child developmentinfluences in improving the skills of mothers to stimulate child development. (Ashri et al. 2017) From theresults of a preliminary study, in 2 PAUD in West Bogor, there were 10% of children under five with doubtfuldevelopment, and 5% of children under five with developmental deviations. This study aims to determine theeffect of fan stimulation of child development in mothers with parenting to the development of toddlers in thecity of Bogor. The design of this study used a survey with a pre and post test design without control groupdesign in which the independent and dependent variables were measured simultaneously. In this study thesampling technique used was simple random sampling. . Variables are measured by questionnaire. Dataanalysis using chi square test. The results showed there was a relationship between the use of fandevelopmental stimulation in the mother with authotarian, permissive and authoritative parenting to monitorthe growth and development of children with a pvalue> 000.5. Suggestions. The use of stimulation fansshould be applied in PAUD / TK schools which are done by the teacher by giving counseling beforehand.